Individual decision-making and cooperation in freshwater fisheries management at the Somme River, northern France - Khumalo, Brian (Rhodes University, Faculty of Humanities, Department of Anthropology)
Are altruistic individuals more likely to cooperate when exploiting common resources? This research study asks whether or not rates of human altruistic behaviour expressed by individual recreational fishers in interpersonal contexts at the Somme River, Amiens mirror those rates of altruism expressed in collective contexts concerning local fisheries resources. In a natural resources context, altruism manifests as a willingness by fishers to incur personal cost for common-pool resource benefit. Accordingly, it is understood that altruistic behaviour reflected collectively expresses itself as cooperation. The research study takes place in Northern France with the stated objectives to: 1) observe individual fishers' altruistic propensities in interpersonal contexts involving other fishers, 2) observe individual rates of altruistic behaviour in collective contexts involving common fisheries resources and compare with those expressed interpersonally, and 3) investigate whether or not a local (informal) management system existed in the town of Amiens to better understand if informal tenure of water space influences altruistic behaviour or not. The research design consists of two components, one quantitative and one qualitative. The former employs two economic games; a Dictators Games (DG) and a Public Good Game (PGG) in service of the first and second research objectives, and the latter employs cognitive mapping and free-listing exercises in service of the third. Here economic games stand as proxies for real-world situations involving individual (DG) and collective (PGG) decision-making whereas the exercises seek to uncover local ecological knowledge (LEK). The results found that while individual recreational fishers demonstrated lower rates of interpersonal altruism overall, in a collective setting involving local fisheries resources the rate was higher, implying a greater willingness to incur personal cost. Ecological knowledge was high among experienced fishers, yet no knowledge pertaining to parallel management and or informal rules of exclusion or resource subtraction were observed, suggesting an informal management system did not exist. The study additionally documents freshwater biodiversity, providing an index of fish species present in the river collected from the free-listing exercises, categorized into native and non-native as the latter can negatively affect trophic systems and ecosystem processes.
Keywords: Fishery management -- France -- Somme River; Fisheries -- France -- Somme River; Human ecology -- France -- Somme River; Traditional ecological knowledge -- France -- Somme River; Decision making; Experimental economics; Recreation -- France -- Somme River